2016
DOI: 10.3329/jdmc.v24i1.29563
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Acinetobacter Spp. Blood Stream Infection in A Neonatal Intensive Care Unit of An Urban Specialized Hospital in Dhaka

Abstract: colistin, imipenem, amikacin, gentamycin, levofloxacin, ciprofloxacin, piperacillin tazobactum and cotrimoxazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Our results were supported by study of Hannan et al (17) as they demonstrated that K. pneumoniae (n=40) and Coagulase-negative staphylococci (CoNS) (n=11) were the most common isolates. Akter et al (18) found that organisms isolated from the blood of the newborn are Acinetobacter spp. 32 (34.48%), followed by Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were supported by study of Hannan et al (17) as they demonstrated that K. pneumoniae (n=40) and Coagulase-negative staphylococci (CoNS) (n=11) were the most common isolates. Akter et al (18) found that organisms isolated from the blood of the newborn are Acinetobacter spp. 32 (34.48%), followed by Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%